Phylogeny and distribution of the genus Pikea (Gigartinales, Rhodophyta) with special reference to P. yoshizakii from Korea. Issue 1 (1st January 2016) - Boo, Ga Hun; Hwang, Il Ki; Ha, Dong Su; Miller, Kathy Ann; Kogame, Kazuhiro; Cho, Ga Youn; Kim, Jung Yeon; Boo, Sung Min
Abstract: Four species have been described in the genus Pikea (Dumontiaceae, Gigartinales): three species from North America and one species from Japan. However, the phylogeny and species delimitation in Pikea remain poorly resolved. Here we provide both rbc L and cox 1 sequences for all species of Pikea, including the type of P. pinnata and a paratype of P. robusta . Our data reveal that P. californica, P. pinnata and P. yoshizakii are distinct in both data sets, but P. robusta is synonymous with the earlier-described P. pinnata . Morphological and molecular data show that Pikea from Korea is identical to P. yoshizakii and that the previous report of P. californica in Korea is a misidentification. The genus Pikea is well resolved in the main clade of the Dumontiaceae. This is the first study on the phylogeny of Pikea using rbc L and cox 1 sequence data.